Late Bronze Age painted pottery traditions at the margins of the Hittite state : papers presented at a workshop held at the 11th ICAANE (München 4 April 2018) and additional contributions - Manuelli, Federico, 1975-; Mielke, Dirk Paul (Archaeopress Publishing, 2022)
The intent of this volume is to break through the boundaries usually imposed by the study of 2nd millennium BC pottery production in Anatolia.12 papers of leading specialists working on relevant material offer, for the first time, the possibility of a deeper understanding of the phenomenon of painted pottery in the 2nd millennium BC.